Identifying selection signatures for litter size in Guangxi Bama Xiang pigs. Issue 12 (29th August 2022) - Mo, Jiayuan; Lu, Yujie; GangYan,; Wang, Yubing; Zhang, Kun; Zhang, Shuai; Wang, Mengying; Chen, Xingfa; Lan, Ganqiu; Liang, Jing
Abstract: Litter size is an important economic trait in pig production. However, the genetic mechanisms underlying varying litter size in Guangxi Bama Xiang pigs remain unknown. To identify selection signatures for litter size in Guangxi Bama Xiang pigs, we obtained 297 Illumina PorcineSNP50 BeadChip array data and the average born number (ABN) from parity one to nine in Guangxi Bama Xiang pigs. Fixation index (Fst) methods were used to identify the selection signature of the litter size, and three phenotypic gradient differential population pairs (according to the ABN) in individuals were used to reduce the false positives of signature selections. Single nucleotide polymorphisms (SNPs) were identified in the VEGFA promoter and exons. The general linear model was used to analyse the differences in distinct genotypes after they were typed using three‐round multiplex PCR technology. Finally, the transcriptome factor and CpG island in the VEGFA promoter were predicted. A total of 328, 328 and 317 significant loci were identified in the 1st, 2nd and 3rd population pairs, respectively. After removing the false positives, 25 SNPs were defined as the selection signatures in relation to litter size. Ten ( VEGFA, USP49, USP25, SRPK1, SLC26A8, RPL10A, PPARD, MAPK14, HMGA1 and CHRDL2 ) out of 52 genes in the selection regions were annotated as the candidate genes of litter size, respectively, VEGFA . There were no SNPs in the VEGFA exon region, but we obtained three SNPs (rs786889605, rs343769603 and rs323942424) in the VEGFA promoter regions. The ABN in CC was significantly higher than that in TT in rs786889605, and the ABN in TT was significantly lower than that in GG in rs323942424. Meanwhile, the mutation of the VEGFA promoter result in the loss of Sp1 and NF‐1 and the formation of Oct‐1. In summary, we obtained ten candidate genes, and two mutations in the VEGFA promoter that could be important potential molecular biomarkers for litter size in Bama Xiang pigs.